A latex slide agglutination test for rapid detection of antimyeloperoxidase antibody. - Ko, K H (1999)
AIM: To develop and test a new latex slide agglutination test (MPO-LSAT) to detect antimyeloperoxidase (anti-MPO) antibody in serum. METHODS: Latex bead coating was adjusted to give maximum sensitivity by attending to latex size, MPO to latex ratio for coupling, ratio of diluted serum to MPO-latex, reaction time and temperature for coupling, and reaction time for agglutination. Inhibition studies were performed using MPO, proteinase 3, bactericidal/permeability increasing protein, and lactoferrin. RESULTS: There was very good correlation between this test and the conventional anti-MPO enzyme linked immunosorbent assay (ELISA): 81% of sera positive in the ELISA were positive by MPO-LSAT. MPO-LSAT results correlated better with IgM anti-MPO than with IgG anti-MPO. CONCLUSIONS: MPO-LSAT is a simple diagnostic test that is potentially useful in the clinical laboratory as a rapid screening tool for vasculitic diseases.